2021
DOI: 10.3390/ijms22052507
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Justicidin B Pathway and Production in Linum austriacum

Abstract: Lignans are the main secondary metabolites synthetized by Linum species as plant defense compounds but they are also valuable for human health, in particular, for novel therapeutics. In this work, Linum austriacum in vitro cultures, cells (Cc), adventitious roots (ARc) and hairy roots (HRc) were developed for the production of justicidin B through elicitation with methyl jasmonate (MeJA) and coronatine (COR). The performances of the cultures were evaluated for their stability, total phenols content and antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 82 publications
3
7
2
Order By: Relevance
“…The metabolic and growth kinetics differences in HR lines depend on the site of integration of T-DNA into the plant genome [ 51 ]. In this work, we confirmed the transformation of the putative HR after the molecular detection of genes rolC (which must be present) and virC1 (a strictly bacterial gene which must be absent); this combination was firstly reported in Salvia species in S. wagneriana and in other species, as Linum austriacum , for instance [ 49 , 52 ].…”
Section: Discussionsupporting
confidence: 77%
“…The metabolic and growth kinetics differences in HR lines depend on the site of integration of T-DNA into the plant genome [ 51 ]. In this work, we confirmed the transformation of the putative HR after the molecular detection of genes rolC (which must be present) and virC1 (a strictly bacterial gene which must be absent); this combination was firstly reported in Salvia species in S. wagneriana and in other species, as Linum austriacum , for instance [ 49 , 52 ].…”
Section: Discussionsupporting
confidence: 77%
“…Regarding the use of elicitors to increase the ATLs production in Linum , we can conclude that both MeJA and COR were appropriate to activate the lignans pathway, as previously reported for other Linum species [ 32 , 33 , 34 ]. The same elicitors were also able to enhance the arylnaphtalenic production in L. austriacum [ 42 ]. Our studies showed that MeJA is more effective on L. mucronatum ARc and 1µM COR on L. flavum ARc.…”
Section: Discussionmentioning
confidence: 99%
“…The hairy roots formation was induced from leaf explants of in vitro seedlings of L. lewisii incubated with Agrobacterium rhizogenes strain ATCC 15,834 following the protocol described in Mascheretti et al 2020 [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, at present, few efforts to produce bioactive molecules from large-scale cell cultures have been commercialized [ 40 ]. Regarding Linum , several attempts to scale up the production have been made, but none of them have yet led to the commercialization of these molecules from cell cultures [ 41 , 42 ]. In order to assess whether L. lewisii cultures could be suitable for future large-scale production, an explorative experiment using a pilot-scale bioreactor has been performed.…”
Section: Introductionmentioning
confidence: 99%